New technologies for ammonium dinitramide based monopropellant thrusters – The project RHEFORM. (February 2018) - Negri, Michele; Wilhelm, Marius; Hendrich, Christian; Wingborg, Niklas; Gediminas, Linus; Adelöw, Leif; Maleix, Corentin; Chabernaud, Pierre; Brahmi, Rachid; Beauchet, Romain; Batonneau, Yann; Kappenstein, Charles; et al.
Abstract: New technologies are developed in the project RHEFORM to enable the replacement of hydrazine with liquid propellants based on ammonium dinitramide (ADN). The replacement of hydrazine with green propellants will make space propulsion more sustainable and better suitable for the requirements of future missions. In the RHEFORM project investigation on the composition of the propellants are conducted to enable the use of materials for catalysts and combustion chambers which are not subject to the International Traffic in Arms Regulations (ITAR). New igniters are under development aiming at a reduction of required energy and a more prompt ignition. Two different types of igniters are considered: improved catalytic igniters and thermal igniters. The technologies developed in RHEFORM will be implemented in two thruster demonstrators, aiming at a technology readiness level (TRL) of 5. In the present work the results obtained in the first half of the project are presented. Highlights: The influence of increased water content in the two baseline propellants was analyzed. Different ignition methods to reduce preheating time were considered. Several catalyst support materials were tested in a batch reactor. Ceramic monolithic catalyst supports were 3D printed with a novel technology. Thermal ignition methods, i.e. laser, resistive and torch ignition were tested.